“Solo cantando estuviera” (If I were singing along): small verses from Piura’s highlands - Figueroa Luna, Guillermo (2018)
This research aimed to understand some features of artistic expression called «rhymes» in the culture of the peasants from the top of the district of Yamango, Morropón province, in the Sierra of the department of Piura, Peru. Participant observation method was applied to collect and classify achieving 212 octosyllabic quatrains sung in local festivals and family. Those «rhymes», composed by themselves or learned on their trips to various places, are sung at their parties or recited in everyday life, they are similar to the «pechadas » of the Sierra of Cajamarca and cumananas of coastal zones of Piura and Lambayeque. Refer to family relationships, romantic love, the difficulties of life, uprooting and death.